Development of a general sustainability indicator for renewable energy systems: A review - Liu, Gang (Renewable & sustainable energy reviews, 2014)
Renewable energy is considered as a solution for mitigating climate change and environmental pollution; however, an important problem of the application of renewable energy systems (RESs) is that the evaluation of the sustainability of these systems is extremely complex. In order to assess the sustainability of renewable energy systems comprehensively, the use of sustainability indicators (SIs) is often necessary. Since sustainability indicators are necessary to reflect various aspects of sustainability, the development of a general sustainability indicator (GSI) including many basic sustainability indicators (BSIs) becomes critical. In this paper, the methods of selection, quantification, evaluation and weighting of the basic indicators as well as the methods of GSI aggregation are reviewed. The advantages and disadvantages of each method are discussed. Based on these discussion and the analysis of the uncertainties of sustainability assessment, an effective framework and its procedures of the development of GSI for renewable energy systems is presented. This GSI is not only able to evaluate all the sustainability criteria of RESs, but also can provide numerical results of sustainability assessment for different objective systems. The proposed framework in this study can be used as a guidance of the development of sustainability indicator for various renewable energy systems.